2023
DOI: 10.1038/s41419-023-06139-7
|View full text |Cite
|
Sign up to set email alerts
|

SCF and IL-33 regulate mouse mast cell phenotypic and functional plasticity supporting a pro-inflammatory microenvironment

Rosa Molfetta,
Mario Lecce,
Nadia D. Milito
et al.

Abstract: Mast cells (MCs) are multifaceted innate immune cells often present in the tumor microenvironment (TME). Several recent findings support their contribution to the transition from chronic inflammation to cancer. However, MC-derived mediators can either favor tumor progression, inducing the spread of the tumor, or exert anti-tumorigenic functions, limiting tumor growth. This apparent controversial role likely depends on the plastic nature of MCs that under different microenvironmental stimuli can rapidly change … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…Moreover, genes associated with lymphocyte cytotoxicity were upregulated in the absence of MCs, suggesting that these cells promote immunosuppression [ 83 ]. These results support in vitro and in vivo evidence demonstrating a role for tumor-infiltrating MCs in favoring a suppressive microenvironment and/or in promoting tumor growth [ 69 , 84 , 85 , 86 , 87 ].…”
Section: Exploring Intestinal Mast Cells’ Role In Tumor Biology: Colo...supporting
confidence: 86%
“…Moreover, genes associated with lymphocyte cytotoxicity were upregulated in the absence of MCs, suggesting that these cells promote immunosuppression [ 83 ]. These results support in vitro and in vivo evidence demonstrating a role for tumor-infiltrating MCs in favoring a suppressive microenvironment and/or in promoting tumor growth [ 69 , 84 , 85 , 86 , 87 ].…”
Section: Exploring Intestinal Mast Cells’ Role In Tumor Biology: Colo...supporting
confidence: 86%
“…Furthermore, it is worth noting that Molfetta et al. demonstrated that sustained stimulation of SCF promotes the proliferation of connective tissue-like mast cell subpopulations and maintains a pro-inflammatory microenvironment in the body, which may also be one of the potential factors contributing to the development of osteonecrosis lesions ( 63 ). Interestingly, however, the positive effects of SCF on osteogenesis, possibly through the c-Kit-Akt signaling pathway, have been recognized in recent years, which may also suggest that SCF may have beneficial effects on osteonecrosis repair ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated the potent enhancing effect of SCF on osteoclast activity in vitro (61), and glucocorticoids, one of the causative agents of pharmacologic osteonecrosis, also increase the expression of SCF in various ways (62), which may reveal one of the key pathogenetic mechanisms of drug-induced osteonecrosis. Furthermore, it is worth noting that Molfetta et al demonstrated that sustained stimulation of SCF promotes the proliferation of connective tissue-like mast cell subpopulations and maintains a pro-inflammatory microenvironment in the body, which may also be one of the potential factors contributing to the development of osteonecrosis lesions (63). Interestingly, however, the positive effects of SCF on osteogenesis, possibly through the c-Kit-Akt signaling pathway, have been recognized in recent years, which may also suggest that SCF may have beneficial effects on osteonecrosis repair (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…These CSC are pivotal in tumor recurrence, occurrence, and metastasis ( Yao et al, 2023 ). Because of their limited number and location in oxygen-deprived tissue far from the blood vessels, it is difficult for drugs to kill CSCs ( Molfetta et al, 2023 ). The survival and stemness maintenance of CSCs depends on the TME.…”
Section: Discussionmentioning
confidence: 99%